2018
DOI: 10.1371/journal.pgen.1007276
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute2 and LaminB modulate gene expression by controlling chromatin topology

Abstract: Drosophila Argonaute2 (AGO2) has been shown to regulate expression of certain loci in an RNA interference (RNAi)-independent manner, but its genome-wide function on chromatin remains unknown. Here, we identified the nuclear scaffolding protein LaminB as a novel interactor of AGO2. When either AGO2 or LaminB are depleted in Kc cells, similar transcription changes are observed genome-wide. In particular, changes in expression occur mainly in active or potentially active chromatin, both inside and outside LaminB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 45 publications
6
33
2
Order By: Relevance
“…First, we transfected NELF-E and CDK9 HA-tagged constructs into Kc cells and performed immunoprecipitation from nuclear extracts followed by Western blotting against AGO2. In concordance with our previous AGO2 mass spec analysis of nuclear interacting factors 3 , we found that NELF-E but not CDK9 associates with AGO2 (Fig. 4A ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…First, we transfected NELF-E and CDK9 HA-tagged constructs into Kc cells and performed immunoprecipitation from nuclear extracts followed by Western blotting against AGO2. In concordance with our previous AGO2 mass spec analysis of nuclear interacting factors 3 , we found that NELF-E but not CDK9 associates with AGO2 (Fig. 4A ).…”
Section: Resultssupporting
confidence: 92%
“…Previously, we showed that AGO2 forms a nuclear complex with Pol II, and chromatin association profiles of both factors correlate positively across chromatin states throughout the genome 3 . These findings prompted us to test whether AGO2 influences Pol II occupancy genome-wide.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations